Female Consumption Drivers Associated with Ride-Hailing in Brazilian Capitals - Violin, Fábio Luciano; Zorzi, Mariciana; Arizaga, Hugo Ferreira; Gouveia, Luiz Borges (Georgetown University Latin America Leadership Program, 2022)
The study proposed an explanatory model of female consumption behavior associated with ride-hailing in Brazil. 2176 interviews were carried out in representative capitals of the five regions of the country, allowing to point out that the use takes place in a utilitarian way with support provided by technological facilitators, evidencing the concern of women with physical and/or psychological violence. The results represent a theoretical advance by revealing the commutability of variables according to the reasons for use and the period of travel, which change the order and degree of importance of the decision-making inductors, indicating that in leisure situations or social obligations in the night, increases the level of relevance of variables related to forms of harassment and self-preservation. Interchangeable behavior is formed by the perception of influence variables associated with reasons for use and time of day and represents a distinctive understanding in understanding the topic.
Impulsores de Consumo Femenino Asociados con Ride-Hailing en Capitales Brasileñas Direcionadores de Consumo Feminino Associados ao Ride-Hailing em Capitais Brasileiras
Keywords: Female consumer behavior; On-demand displacement; Ride-hailing; Technology